Levelling up math literacy through e-contents : an example of portuguese students from Hospitality and Tourism Management Bachelor degrees - Soares, Filomena Baptista (2018)
Despite the global and general Management Area, common to all the bachelor degrees in the School of Hospitality and Tourism (ESHT) from the Polytechnic of Porto (P.PORTO), the pre-university areas admitted for entering these degrees are the most varied, going from Sciences and Technologies to Arts and Humanities. The students' abilities are very heterogeneous and this heterogeneity proves to be very awkward and complex when dealing with specific themes related to Mathematics and to the deductive-logic reasoning that this science involves and develops. In this article, we begin with a brief description of the process for entering into the Higher Education Portuguese System, in particular in ESHT. We describe the different resources developed and available in the institutional Moodle platform, with a reference to the general and specific outcomes and competences expected from Quantitative Methods (QM) course. Then, we analyse the impact of using several e-contents and resources, specifically developed for QM course, in the first semester of the first year (the usual General Mathematics course in any Management Degrees) and try to differentiate the “impact perception” from the background students study field, based on students’ direct assessment and their real learning results. To conclude, the results of the resources evaluation as learning support tools, made by students, are presented and we cross these with the students’ success in this course. These findings suggest that the methodology used in this research could be a promising way of enhancing students’ learning performance.